Peningkatan Keterampilan Menulis Teks Debat melalui Aplikasi YouCut pada Siswa Kelas X SMK Musda Perbaungan - Batubara, Sofia Salsabila; Kartika, Rika; Amaluddin, Amaluddin (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to evaluate the use of the YouCut application in writing debate texts for Class X at SMK Musda Perbaungan. The study involved 481 students, with a sample of 32 students from class X RPL 1. Data collection methods included observation, interviews, and questionnaires. This research used the Borg and Gall research and development (R&D) model, comprising seven stages: needs analysis, media planning, initial product development, small group trials, initial stage revisions, large group trials, and final revision and product finalization. The results indicated that the YouCut-assisted learning media significantly improved students' skills in writing debate texts. Validation by material experts yielded scores of 80% and 81%, while media experts rated it at 80% and 92%. Feasibility tests with teachers and students showed positive results, with Indonesian language teachers scoring it at 92% and students giving an average score of 97%.